Low Levels of Serum Soluble Receptors for Advanced Glycation End Products, Biomarkers for Disease State: Myth or Reality - Prasad, Kailash (International Journal of Angiology, 2014)
Advanced glycation end products (AGEs) interact with the receptor for AGEs (RAGE) on the membrane and induce deleterious effects via activation of nuclear factor kappa-B, and increased oxidative stress and inflammatory mediators. AGEs also combine with circulating soluble receptors (endogenous secretory RAGE [esRAGE] and soluble receptor for RAGE [sRAGE]) and sequester RAGE ligands and act as a cytoprotective agent. esRAGE is secreted from the cells and is a spliced variant of RAGE. The sRAGE on the other hand is proteolytically cleaved from cell surface receptor via matrix metalloproteinase (MMPs). sRAGE is elevated in type 1 and type 2 diabetes and in patients with decreased renal function. Serum levels of sRAGE are reduced in diseases including coronary artery disease, atherosclerosis, essential hypertension, chronic obstructive lung disease, heart failure, and hypercholesterolemia. Serum levels of AGEs are elevated in patients with coronary artery disease and atherosclerosis. However, the increases in serum AGEs are very high in patients with diabetes and renal disease. There is a positive correlation between serum levels of AGEs and RAGE and sRAGE. The elevated levels of sRAGE in patients with diabetes and impaired renal function may be due to increased levels of MMPs. AGEs increase in the expression and production of MMPs, which would increase the cleavage of sRAGE from cell surface. In conclusion, low level of serum sRAGE is a good biomarker for disease other than diabetes and renal disease. A unified formula that takes into consideration of AGEs, sRAGE, and esRAGE such as AGE/sRAGE or AGEs/esRAGE would be better biomarker than sRAGE or esRAGE for all AGE-RAGE–associated diseases including diabetes and renal disease.
Keywords: advanced glycation end products; soluble receptor for AGEs; endogenous secretory receptor for AGEs; biomarker; coronary artery disease; diabetes; renal dysfunction; unified biomarker for AGE-RAGE–associated diseases